PENGARUH ULASAN KONSUMEN (CONSUMER REVIEWS) DAN KEPERCAYAAN KONSUMEN (CONSUMER TRUST) TERHADAP PENCEGAHAN KECURANGAN PEMBELIAN ONLINE - Jamilatul Uyun; Agus Sari (Jurnal Akuntansi dan Keuangan, 2024)
This research aims to determine the influence of consumer reviews and consumer trust on preventing online purchasing fraud. This research method uses quantitative methods by distributing questionnaires. The data analysis used was SPSS 22.0 software. The population in this study were all Master's students at Trunojoyo University, Madura and active undergraduate students at Madura Islamic University who had e-commerce accounts, while the sample selection method used a purposive sampling method, namely 197 samples. The results of the research show that consumer reviews have no effect on preventing online purchase fraud and consumer trust has an effect on preventing online purchase fraud. It is hoped that the results of this research can be a reference for future researchers and can provide knowledge for online shop buyers to be more careful and thorough in carrying out online buying and selling transactions.